Mitochondrial Ca2 + Is Related to Mitochondrial Activity and Dynamic Events in Mouse Oocytes - Wang, Feng; Meng, Tie-Gang; Li, Jian; Hou, Yi; Luo, Shi-Ming; Schatten, Heide; Sun, Qing-Yuan; Ou, Xiang-Hong (Frontiers in Cell and Developmental Biology, 2020)
Mitochondrial energy insufficiency is strongly associated with oocyte activation disorders. Ca2+, especially that in the mitochondrial matrix, plays a pivotal role in mitochondrial energy supplementation, but the underlying mechanisms are still only poorly understood. An encoded mitochondrial matrix Ca2+ probe (Mt-GCaMP6s) was introduced to observe mitochondrial Ca2+ ([Ca2+]m) dynamic changes during oocyte maturation and activation. We found that active mitochondria surrounding the nucleus showed a higher [Ca2+]m than those distributed in the cortex during oocyte maturation. During oocyte partheno-activation, the patterns of Ca2+ dynamic changes were synchronous in the cytoplasm and mitochondria. Such higher concentration of mitochondrial matrix Ca2+ was closely related to the distribution of mitochondrial calcium uptake (MICU) protein. We further showed that higher [Ca2+]m mitochondria around the chromosomes in oocytes might have a potential role in stimulating mitochondrial energy for calmodulin-responsive oocyte spindle formation, while synchronizing Ca2+ functions in the cytoplasm and nuclear area are important for oocyte activation.